Effect of soft drink towards heat cured acrylic resin denture base surface roughness - Sofya, Pocut Aya; Rahmayani, Liana; Purnama, Rico Riski Candra (Universitas Padjadjaran, 2017)
Introduction: The absorption of fluid in the heat cured acrylic resin is able to cause the increase in surface roughness. Absorption of acidic fluid such as soft drinks can cause even higher increase of surface roughness. The objective of this study was to determined the effect of soft drinks towards heat cured acrylic resin denture base surface roughness. Methods: Specimens of this study were 32 pieces of specimen with the size of 12×12×3 mm. Sixteen pieces of specimens were kept in aquadest as a control group and 16 pieces of specimens were immersed in the soft drinks as the treatment group. Initial surface roughness was measured using surface roughness tester. The specimens were then immersed in both immersion media for 2 days. After immersion, the surface roughness of specimens were measured again. Results: Data obtained on the roughness measurements were analyzed using paired t test with the results of the analysis showed a significant difference (p<0.05). Conclusion: It was concluded that there was increased in heat cured acrylic resin denture base surface roughness after immersed in soft drinks solvent.